MODEL PENDIDIKAN PROFETIK NABI MUHAMMAD SAW DI MADINAH: TRANSFORMASI SOSIAL DAN REKONSTRUKSI EPISTEMOLOGI ISLAM - Fanni Febria; Wilaela Wilaela (STKIP Subang, 2026)
This study aims to analyze the prophetic educational model of the Prophet Muhammad SAW in Medina from the perspective of social transformation and the reconstruction of Islamic epistemology. The research is motivated by various contemporary educational problems, such as the dichotomy of knowledge, moral crisis, and the weakening integration between the spiritual, intellectual, and social dimensions. This study uses a qualitative approach with library research. Data were obtained from various relevant contemporary scientific literature. Data analysis was conducted through content analysis with historical, philosophical, and socio-pedagogical approaches. The results show that the prophetic educational model of the Prophet Muhammad SAW in Medina was built through education based on monotheism, exemplary behavior, humanism, dialogue, and social integration. This educational model successfully transformed Medina society from a society fragmented by tribal conflict to a society that is civilized, just, and oriented towards knowledge. The reconstruction of Islamic epistemology was carried out through the integration of revelation, reason, and social experience, resulting in a holistic and transformative paradigm of knowledge. The existence of al-Suffah as a center of learning at the Prophet's Mosque strengthened the educational process by producing generations of knowledgeable and moral companions, such as Abu Hurairah, who played a crucial role in the transmission of Islamic knowledge. This study concludes that the prophetic education of the Prophet Muhammad (peace be upon him) in Medina is an integral educational model relevant to the development of contemporary Islamic education in addressing moral, social, and epistemological challenges.